Characteristics of premonitory urge and tic symptom in different age groups from a network perspective - Yu, Liping; Li, Yanlin; Wang, Xianbin; Cui, Yonghua (Frontiers in Psychiatry, 2025)
BackgroundTic disorders are neurodevelopmental disorders. Current research suggests that premonitory urges (PU) may be the cause and basis of tic disorders. The study used network analysis to investigate the detailed associations between PUs and tic symptoms the and internal relationships of PUs.MethodsWe included 1021 outpatient tic disorders. We used R 4.1.3 to perform network analysis. The “qgraph” package constructed the Premonitory Urge for Tics Scale (PUTS) and Yale Global Tic Severity Scale (YGTSS)networks for low-age and high-age group, and calculated the centrality measures for the four networks. We used the “bootnet” package to test the accuracy of the four network models and used the “NetworkComparisonTest” package to compare the networks for different age groups.ResultsThe network structures were stable (above 0.5). The node with the highest intensity was the 8th entry. The “connection” node was identified as the “all defects caused by motion or vocal tics” entry in the YGTSS. The strength and weight of the network structures did not significantly differ between the different groups. The node strength substitution test revealed that the 9th item had a significantly stronger intensity in lower age group (0.75) than in the higher age group (0.53) with a P-value of 0.03. The strength in the network was also significantly greater in the younger age group (1.34) than in the older age group (1.02) with a P-value of 0.04.ConclusionThis study validates the internal structure of the PUTS scale across different age groups from a network perspective. It provides theoretical guidance and practical basis for targeted behavioral therapy.